The Relationship Between Chemical Awareness Chemical Safety Among the First Year Students of Engineering Campus, Universiti Sains Malaysia - Faris, Abdullah (2012)
The study conducted is meant to investigate the correlation between risk control, awareness on chemical hazards and awareness on chemical risks with chemical safety among first year students of Engineering Campus of Universiti Sains Malaysia. A total of 174 students from three programs of studies which are Chemical Engineering, Civil Engineering and Material and Mineral Resources Engineering completed the 45 item questionnaire. Significant correlation between risk control, awareness on chemical hazards and awareness on chemical risks with chemical safety were established. However, it is also found that there was no significant difference reported by male and female gender towards chemical safety. This is most probably both gender, male and female have same perception towards chemical safety. Other than that, it is also found that there is a significant different in education level of the respondents towards chemicals safety. It is discovered that the strongest association is between risk control and safety precautions with chemical safety while the weakest connection is between awareness on chemical risks with chemical safety. Therefore, the current programs of occupational safety and health in Engineering Campus, Universiti Sains Malaysia is found to be effective and there are still rooms for improvement in order to increase the awareness level among the first year students. Proactive measures can be taken in order to enhance and to boost the current level of awareness.